2000
DOI: 10.1136/bmj.320.7248.1517
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of studies of patient satisfaction with telemedicine

Abstract: Objective To review research into patient satisfaction with teleconsultation, specifically clinical consultations between healthcare providers and patients involving real time interactive video.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
473
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(527 citation statements)
references
References 34 publications
42
473
0
12
Order By: Relevance
“…Several studies have shown the feasibility and cost-effectiveness of using telemedicine in orthopaedics [3-6, 8, 17, 20, 21], and similar to our results, they report high levels of patient satisfaction. Mair and Whitten [11] conducted a systematic review of studies that involved a patient-satisfaction measure with telemedicine interventions. They reviewed 32 studies across any discipline and concluded that, although the majority report high levels of patient satisfaction, these studies also had many methodologic deficiencies, such as study design and low sample sizes, that limit the validity and generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the feasibility and cost-effectiveness of using telemedicine in orthopaedics [3-6, 8, 17, 20, 21], and similar to our results, they report high levels of patient satisfaction. Mair and Whitten [11] conducted a systematic review of studies that involved a patient-satisfaction measure with telemedicine interventions. They reviewed 32 studies across any discipline and concluded that, although the majority report high levels of patient satisfaction, these studies also had many methodologic deficiencies, such as study design and low sample sizes, that limit the validity and generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although obtaining indications of satisfaction is an important operational aspect for telemedicine programs, satisfaction is not regarded as a strong measure of outcome. 6 Also, we did not include, for the purposes of this project, studies that reported outcomes only for caregivers and not for patients.…”
Section: Methodsmentioning
confidence: 99%
“…The use of technology has become a cost-effective avenue to deliver quality healthcare [22]. The potential of information technology in enhancing an individual's access to healthcare has been regarded as a promising innovation that might revolutionise healthcare [23].…”
Section: Introductionmentioning
confidence: 99%